A cross-sectional household cluster serosurvey of hepatitis C virus antibodies in an urban slum of Cairo, Egypt in 2004. Issue 1 (December 2015) - Nakhla, Isabelle; Sanders, John; Mohareb, Emad; Samy, Sahar; Cosby, Michael; Mostafa, Manal; Riddle, Mark; Frenck, Robert
Abstract Background Hepatitis C Virus (HCV) continues to be a burden to the Egyptian population and its economy. Despite all efforts, the prevalence of infection continues to be one of the highest in the world. The high national prevalence has been attributed to unintentional, nosocomial spread during an anti-schistosomiasis campaign conducted in the 1970's, but that does not fully explain the persistent infection rates. Work is needed to further clarify risk associations. A serosurvey was performed in Manshiet Nasser, a slum in Cairo sometimes referred to as Mokattem Hills where a primary occupation is garbage collection and sorting, to characterize potential risk factors for infection. Methods Following a detailed mapping and census of the area, a cluster sampling was performed and demographic and risk behavior data and a blood sample were collected from subjects older than 6 months. Blood samples were tested using 4th generation anti-HCV EIA kit. Results The slum was estimated to house 45, 000 residents. Blood samples were obtained from 2169 subjects. The age adjusted anti-HCV seroprevalence was 9.1 %. Participants with HCV antibodies were more likely to be male, heads of households, subjects without formal education, and those with a lower standard of living. After adjustment of all prevalence ratios (aPR) for age, the following risk factors were significantly associated with higher risk of HCV infection: Garbage collection (aPR 1.5), history of blood transfusion (aPR 2.0), tattooing (aPR 1.4), history of schistosomiasis (aPR 1.5), and use of traditional latrines (aPR 2.0) or pits for sanitation (aPR 1.3). The results of the multivariate analysis indicated that age (p < 0.01), history of schistosomiasis (p < 0.05), garbage sorting (p = 0.05), blood transfusions (<0.001), and the use of traditional latrines for sanitation (p < 0.01) were significantly associated with infection. Conclusion While HCV prevalence among those over 30 could be attributed to anti-schistosomiasis injections, the prevalence in younger age indicates ongoing transmission. Although specific behavioral risks were not identified, HCV infection appears to be an occupational hazard of garbage collection and sorting in this environment. Given the large reservoir of HCV infection in the population, further effort needs to be made to identify and mitigate new infections.